Population genetic structure in the invasive ant Tapinoma indicum (Forel) (Hymenoptera: Formicidae) in Penang Island, Malaysia - Li, Yang Lim; Li, Lim; Abdul Hafiz Ab Majid, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Tapinoma indicum (Forel, 1895) (Hymenoptera: Formicidae) is a common household ant in Southeast Asia and has become increasingly dominant in urban environments on Penang Island, Malaysia. Its ability to establish persistent infestations indoors presents a growing concern. As its presence expands, understanding its genetic structure and dispersal patterns becomes increasingly important to uncover how it colonizes new areas and maintains high population densities. This study presents the first population genetic analysis of T. indicum using seven polymorphic microsatellite markers. A total of 300 individuals from 30 residential sites across three districts were analyzed to assess genetic diversity and population structure. All loci exhibited high polymorphism, with an average of 31 alleles per locus and high expected heterozygosity (mean HE = 0.926), indicating substantial genetic variation. However, observed heterozygosity was lower (mean HO = 0.437), and some loci showed signs of null alleles and inbreeding. F-statistics revealed moderate inbreeding within populations (mean FIS = 0.490) and low genetic differentiation between districts (FST = 0.075). Principal Coordinates Analysis and STRUCTURE results showed weak spatial genetic structuring and evidence of admixture, suggesting widespread gene flow. These findings indicate that T. indicum populations on Penang Island are genetically diverse but not strongly differentiated, forming a largely interconnected population across the island.